2011
DOI: 10.1016/j.nima.2010.12.145
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the ISOLDE acceleration voltage using a high-precision voltage divider and applying collinear fast beam laser spectroscopy

Abstract: A high-voltage divider with accuracy at the ppm level and collinear laser spectroscopy were used to calibrate the highvoltage installation at the radioactive ion beam facility ISOLDE at CERN. The accurate knowledge of this voltage is particularly important for collinear laser spectroscopy measurements. Beam velocity measurements using frequencycomb based collinear laser spectroscopy agree with the new calibration. Applying this, one obtains consistent results for isotope shifts of stable magnesium isotopes mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…This novel technique has recently been applied for the first time at an ISOL facility. As was reported at the Poznan conference by Krieger et al [69], deviations of −12 V and +39 V were found from the reading of the high voltage divider for the two ISOLDE 60 kV power supplies. At the Poznan conference, Rudolfo Sanchez reported on the absolute frequency measurement of the 2s → 3s transition in the stable lithium-6 and lithium-7 isotopes [70].…”
Section: Trends and Future Directionssupporting
confidence: 71%
“…This novel technique has recently been applied for the first time at an ISOL facility. As was reported at the Poznan conference by Krieger et al [69], deviations of −12 V and +39 V were found from the reading of the high voltage divider for the two ISOLDE 60 kV power supplies. At the Poznan conference, Rudolfo Sanchez reported on the absolute frequency measurement of the 2s → 3s transition in the stable lithium-6 and lithium-7 isotopes [70].…”
Section: Trends and Future Directionssupporting
confidence: 71%
“…For voltages of up to 35 kV they provide a long-term stability of < 10 −6 per month as well as negligible temperature and voltage dependencies [149]. The two dividers have served recently to calibrate the ISOLDE facility at CERN [156]. The permanent voltage monitoring with the precision voltage divider and frequent 83m Kr calibration measurements at the monitor spectrometer will provide reliable and stable calibration and monitoring for the retarding potential of the main spectrometer over long periods of time.…”
Section: Overview: Pre-filtering and Precision Scanningmentioning
confidence: 99%
“…For the KATRIN-experiment these dividers will precisely measure the retarding potential (-18.6 kV) of the spectrometer over five years of measurement time in which the precision of 3 ppm is required for a period of two month [1]. The K35 and K65 were also used to calibrate the acceleration voltage of the ISOLDE facility at CERN [8].…”
Section: Introductionmentioning
confidence: 99%